The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/01.shk.0000135287.16417.5a
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyethyl Starch Produces Attenuation of Circulatory Shock and Cerebral Ischemia During Heatstroke

Abstract: We hypothesized that hydroxyethyl starch (HES), which maintains colloid osmotic pressure and potentially "seals" capillary leaks, would ameliorate circulatory shock and cerebral ischemia during heatstroke in a rat model. Animals under urethane anesthesia were exposed to high ambient temperature (Ta) of 42 degrees C until mean arterial pressure and local cerebral blood flow in the striatum began to decrease from peak level, which was arbitrarily defined as the onset of heatstroke. Control rats were exposed to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
3
19
1
Order By: Relevance
“…When rodents are exposed to external heat stress, they have both decreased stroke volume and decreased peripheral vascular resistance produced arterial hypotension (28). Both arterial hypotension and intracranial hypertension eventually led to cerebral hypoperfusion and hypoxia after the onset of heatstroke, as demonstrated in the present results.…”
Section: Discussionsupporting
confidence: 64%
“…When rodents are exposed to external heat stress, they have both decreased stroke volume and decreased peripheral vascular resistance produced arterial hypotension (28). Both arterial hypotension and intracranial hypertension eventually led to cerebral hypoperfusion and hypoxia after the onset of heatstroke, as demonstrated in the present results.…”
Section: Discussionsupporting
confidence: 64%
“…24,25,27) Excessive accumulation of glutamate has been shown in ischemic brain tissue. 28,29) Indeed, both present and previous results 7,37) have demonstrated that extracellular levels of glutamate, glycerol and lactate/pyruvate in ischemic brain are greater in heat stroke rats compared with those of normothermic controls. Meanwhile, evidences of histopathological morphology and neuronal damage score also reveal severe neuronal damage (shown in Fig.…”
Section: Disscusionmentioning
confidence: 80%
“…22,35,36) There is evidence that cerebral ischemia (due to arterial hypotension and intracranial hypertension) may be one of the major causes to induce further damage after heat stroke onset. 14,19,37) After heat stroke induction, the CBF is instantly drops from highest peak, and it is concomitant with significant increments of cerebral ischemia and injury indexes, as shown in Fig. 1.…”
Section: Disscusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overproduction of NO may contribute to the splanchnic vasodilation that precedes vascular collapses with heatstroke. Our previous results have further shown that in addition to overproduction of NOx in brain, decreased cardiac output (due to decreased total peripheral vascular resistance and stroke volume), intracranial hypertension, and cerebral ischemia and hypoxia, and hyperthermia occur during heatstroke in the rat (10,11,21). Our previous findings have also shown that accumulation of large amounts of reactive oxygen species in various organs including the kidney and the brain is associated with hyperthermia, arterial hypotension, and cerebral ischemia and injury during heatstroke (22,23).…”
Section: Discussionmentioning
confidence: 99%